2022
DOI: 10.1016/j.jvoice.2020.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wearing a Face Mask on Vocal Self-Perception during a Pandemic

Abstract: Objective To analyze the vocal self-perception of individuals who wore face masks for essential activities and those who wore them for professional and essential activities during the coronavirus disease pandemic. Materials and Methods This was an observational, descriptive, cross-sectional study. The study included 468 individuals who were stratified into two groups: the Working Group, comprising individuals who wore face masks for professional and essential activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
1
23

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 29 publications
3
95
1
23
Order By: Relevance
“…Although HNR and CPPS actually reflect different phenomena in voice quality 49 , the non-significant changes in CPPS and vocal intensity across conditions did not appear to support www.nature.com/scientificreports/ the compensation assumption. In addition, phonation compensation in mask wearing may include increased vocal effort, as reported in a previous study 13 . Increased vocal effort seems associated with a different trend of spectral change.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Although HNR and CPPS actually reflect different phenomena in voice quality 49 , the non-significant changes in CPPS and vocal intensity across conditions did not appear to support www.nature.com/scientificreports/ the compensation assumption. In addition, phonation compensation in mask wearing may include increased vocal effort, as reported in a previous study 13 . Increased vocal effort seems associated with a different trend of spectral change.…”
Section: Discussionmentioning
confidence: 63%
“…A mask also physically creates a visual barrier precluding lip reading 11 , precluding communication cues in people with hearing loss and communication disabilities such as aphasia 12 . From a user's perspective, wearing masks increased perception of vocal effort, reduced auditory feedback, and difficult coordination of speech and breathing 13 . Understanding the aspects of the voice changes whilst wearing a mask is important so clinical decision, making and choice of mask is appropriate to meet infection control and optimal verbal communication.…”
mentioning
confidence: 99%
“…Conversely, using a raised voice, another strategy reported by participants here, can have negative effects for both the talker (vocal fatigue) and the listener (decreased speech intelligibility resulting from the secondary effects of increased vocal effort; Abou-Raf ee et al 2019). Indeed, a recent survey found that users of face coverings reported increased perception of vocal effort, difficulty in speech intelligibility, and difficulty in coordinating speech and breathing (Ribeiro et al 2020).…”
Section: Themesmentioning
confidence: 99%
“…In this new reality, hybrid contexts, in which some activities can be implemented in person and others at a distance, have become common. This context has not been different in the area of speech therapy, and recent research on voice has been dedicated to understanding the following: professional vocal use during this pandemic period, especially in singers (6); the impact of wearing facemasks (7); the risks of vocal changes in different professionals who are working remotely (8,9); and the challenge of virtual voice therapy (10,11). The teacher's voice has been one of the themes most researched by specialists for decades, especially regarding symptoms and risk factors.…”
Section: ' Introductionmentioning
confidence: 99%